Multidisciplinary structural optimization of novel high-aspect ratio composite aircraft wings - Kilimtzidis, Spyridon; Kostopoulos, Vassilis (Structural and multidisciplinary optimization, 2023)
Novel high-aspect ratio airframe designs pave the way for a more sustainable aviation future. Such configurations enhance the aerodynamic efficiency of an aircraft through induced drag reduction mechanisms. Further performance gains, mainly in terms of structural mass, are accomplished via composite materials airframes. Nevertheless, undesired phenomena such as geometric nonlinearities and aeroelastic couplings due to elevated flexibility may often rise, rendering the design and optimization of such airframes extremely intricate and prohibitive in terms of computational cost. Low-fidelity tools, often preferred on the early design stages, accelerate the design process, albeit suffering from reduced accuracy and ability to capture higher-order phenomena. Contrastingly, high-fidelity computational methods incur excessive computational cost and are therefore utilized at the later, detailed design stages. There arises, therefore, the need for a combination of the various fidelities involved in a cost-effective manner, in order to drive the design towards optimal configurations without significant performance losses. In our approach, variable fidelity analyses are initially conducted in order to shed light on their effect on the structural response of a high-aspect ratio composite materials reference wing. An optimization framework combining low and high-fidelity tools in a sequential manner is then proposed, aiming at attaining a minimum mass configuration subject to multidisciplinary design constraints. As demonstrated, reasonable mass reduction was obtained for a future aircraft wing configuration.